Utilization of a species occupancy model for management and conservation - Tiffany M. McFarland; Heather A. Mathewson; Julie E. Groce; Michael L. Morrison; J. Cal Newnam; R. Todd Snelgrove; Kevin L. Skow; Bret A. Collier; R. Neal Wilkins (Wildlife Society Bulletin)
Abstract Conserving habitat is increasingly challenging as human populations grow. Remote‐sensing technology has provided a means to delineate species' habitat on large spatial scales. However, by combining habitat delineations with predictions of species' occurrence, habitat models can provide additional utility applications for conservation by allowing us to forecast how changing environmental and landscape conditions affect species' occurrence and distribution. We demonstrate how a spatially explicit habitat occupancy model for the golden‐cheeked warbler (Setophaga chrysoparia) can be used as an impact assessment and conservation planning tool. We used predictions of patch‐level occupancy rates and created several scenarios that simulated the removal or protection of warbler habitats. Resulting changes to habitat structure and availability were used to assess the resulting impacts of removal or protection on the occurrence probability for remaining habitat patches. By recalculating occupancy based on changes to habitat, our approach provides the ability to assess and compare impacts of location and orientation of development so that the least harmful option relative to predicted occurrence can be chosen. Potential applications of our modeling approach are many because our methods provide a useful tool for identifying potential impacts and assisting with mitigation efforts focused on the conservation and management of a species. © 2012 The Wildlife Society.